Global Health of Babies and Children. Issue 3 (May 2017) - Gennaro, Susan; O'Connor, Caitlin; Marx, Megan
Abstract: Purpose: We provide an overview of the health of neonates, infants, and children around the world. Issues in maximizing neonatal health are examined using the Sustainable Development Goals developed by the United Nations as a framework. Recommendations: Interventions that can help optimize neonatal, infant, and child health in the future are reviewed, including increasing preventative healthcare (immunizations, malaria prevention, exclusive breastfeeding for the first 6 months of life), enhancing point-of-care interventions (including umbilical cord care, antenatal corticosteroids if preterm birth is anticipated, and antibiotic therapy), enhancing nutritional interventions (to decrease diarrheal diseases and decrease wasting, stunting, and underweight), and building systems capacity. Clinical Implications: In an increasingly global world where wars, climate change, civil unrest, and economic uncertainty all influence health, it is important that nurses understand global health problems common for neonates, infants, and children and current recommendations to enhance their health. Abstract : An overview of the health of neonates, infants, and children around the world is presented. Issues in maximizing neonatal health are examined using the framework of the Sustainable Development Goals developed by the United Nations. In an increasingly global world where wars, climate change, civil unrest, and economic uncertainty all influence health, nurses should be aware of common global health problems for babies and children and current recommendations to enhance their health.